Mutational analysis of the eyeless gene and phenotypic rescue reveal that an intact Eyeless protein is necessary for normal eye and brain development in Drosophila. - Clements, J; Hens, K; Merugu, S; Dichtl, B; de Couet, H; Callaerts, P (2009)
Pax6 genes encode evolutionarily highly conserved transcription factors that are required for eye and brain development. Despite the characterization of mutations in Pax6 homologs in a range of organisms, and despite functional studies, it remains unclear what the relative importance is of the various parts of the Pax6 protein. To address this, we have studied the Drosophila Pax6 homolog eyeless. Specifically, we have generated new eyeless alleles, each with single missense mutations in one of the four domains of the protein. We show that these alleles result in abnormal eye and brain development while maintaining the OK107 eyeless GAL4 activity from which they were derived. We performed in vivo functional rescue experiments by expressing in an eyeless-specific pattern Eyeless proteins in which either the paired domain, the homeodomain, or the C-terminal domain was deleted. Rescue of the eye and brain phenotypes was only observed when full-length Eyeless was expressed, while all deletion constructs failed to rescue. These data, along with the phenotypes observed in the four newly characterized eyeless alleles, demonstrate the requirement for an intact Eyeless protein for normal Drosophila eye and brain development. They also suggest that some endogenous functions may be obscured in ectopic expression experiments.